2022
DOI: 10.3847/1538-4357/ac32c6
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Characterize the Wide-angle Point-Spread Function of Astronomical Images

Abstract: Uncertainty in the wide-angle point-spread function (PSF) at large angles (tens of arcseconds and beyond) is one of the dominant sources of error in a number of important quantities in observational astronomy. Examples include the stellar mass and shape of galactic halos and the maximum extent of starlight in the disks of nearby galaxies. However, modeling the wide-angle PSF has long been a challenge in astronomical imaging. In this paper, we present a self-consistent method to model the wide-angle PSF in imag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…Finally, the remaining artifacts brighter than a magnitude of 16 are masked. Further details are provided in van Dokkum et al (2020) and Liu et al (2022).…”
Section: Multiresolution Filteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the remaining artifacts brighter than a magnitude of 16 are masked. Further details are provided in van Dokkum et al (2020) and Liu et al (2022).…”
Section: Multiresolution Filteringmentioning
confidence: 99%
“…In Figure 16, we give the complete subtracted model, including that generated by the MRF procedure. wings Liu et al 2022). To ensure that the tidal break is not the result of Dragonfly's PSF, in Figure 18 we convolve 2D Sérsic models of each galaxy without the break with Dragonfly's wide-angle PSF (as utilized in Section 3.2), and compare to the observed surface brightness profile.…”
Section: Appendix C Isophote Fitting and Model Subtractionmentioning
confidence: 99%
“…Scattered light is the perennial bane of low surface brightness photometry, and edge-on galaxies are especially susceptible to scattered light contamination along the minor axis where the true light distribution may drop off very steeply (de Jong 2008; Sandin 2014Sandin , 2015. The elderflower package 16 (Liu et al 2022) was used to fit a three-component power-law PSF with a Moffat core within a 0°.42 × 0°.42 central cutout of each g-and r-band image. The PSF model was extrapolated to a radius of 0°.…”
Section: Discussionmentioning
confidence: 99%
“…It is advantageous to measure the PSF on the science images themselves, because the PSF is not constant over time. For example, by comparing the PSFs of the M44 field observed on two clear nights immediately before and after the lenses were cleaned, Liu et al (2022) showed that the Dragonfly wide angle PSF is measurably impacted by the cleanliness of the lenses. The pre-cleaning PSF was much shallower than the post-cleaning PSF beyond ¢ 3 , with fitted power-law indices of 1.35 and 1.9 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the characterization of the wide-angle PSF may be sensitive to sky subtraction, particularly in crowded regions (cf. Liu et al 2022). We will improve the telescope's PSF model analysis in future work.…”
Section: Scattering and Reflectionmentioning
confidence: 99%